A universal polymer shell-isolated nanoparticle (SHIN) design for single particle spectro-electrochemical SERS sensing using different core shapes. Issue 22 (30th September 2021) - Boccorh, Delali K.; Macdonald, Peter A.; Boyle, Colm W.; Wain, Andrew J.; Berlouis, Leonard E. A.; Wark, Alastair W.
Abstract : A new design of shell isolated nanoparticles (SHINs) is described that can be applied to various gold core shapes for non-interfering surface-enhanced Raman scattering (SERS) sensing at single nanoparticle resolution in electroactive environments. Abstract : Shell-isolated nanoparticles (SHINs) have attracted increasing interest for non-interfering plasmonic enhanced sensing in fields such as materials science, biosensing, and in various electrochemical systems. The metallic core of these nanoparticles is isolated from the surrounding environment preventing direct contact or chemical interaction with the metal surface, while still being close enough to enable localized surface plasmon enhancement of the Raman scattering signal from the analyte. This concept forms the basis of the shell isolated nanoparticle-enhanced Raman spectroscopy (SHINERS) technique. To date, the vast majority of SHIN designs have focused on SiO2 shells around spherical nanoparticle cores and there has been very limited published research considering alternatives. In this article, we introduce a new polymer-based approach which provides excellent control over the layer thickness and can be applied to plasmonic metal nanoparticles of various shapes and sizes without compromising the overall nanoparticle morphology. The SHIN layers are shown to exhibit excellent passivation properties and robustness in the case of gold nanosphere (AuNP) and anisotropic gold nanostar (AuNS) core shapes. In addition, in situ SHINERS spectro-electrochemistry measurements performed on both SHIN and bare Au nanoparticles demonstrate the utility of the SHIN coatings. Correlated confocal Raman and SEM mapping was achieved to clearly establish single nanoparticle SERS sensitivity. Finally, confocal in situ SERS mapping enabled visualisation of the redox related molecular structure changes occurring on an electrode surface in the vicinity of individual SHIN-coated nanoparticles.